Reporting, predictive analytics, and everything in between : a guide to selecting the right analytics for you - Stupakevich, Brett; Sweenor, David; Swiderek, Shane (O'Reilly Media, Inc., 2019)
Business decisions today are tactical and strategic at the same time. How do you respond to a competitor's price change? Or to specific technology changes? What new products, markets, or businesses should you pursue? Decisions like these are based on information from only one source: data. With this practical report, technical and non-technical leaders alike will explore the fundamental elements necessary to embark on a data analytics initiative. Is your company planning or contemplating a data analytics initiative? Authors Brett Stupakevich, David Sweenor, and Shane Swiderek from TIBCO guide you through several analytics options. IT leaders, product developers, analytics leaders, data analysts, data scientists, and business professionals will learn how to deploy analytic components in streaming and embedded systems using one of five platforms. You'll examine: Analytics platforms including embedded BI, reporting, data exploration & discovery, streaming BI, and data science & machine learning The business problems each option solves and the capabilities and requirements of each How to identify the right analytics type for your particular use case Key considerations and the level of investment for each analytics platform.